Torsion Stability and Performance of Re-entrant Irregular Multistory Structures with Optimal Shear Wall Strengthening - Ghivari Alkindy; Resmi Bestari Muin (Rekayasa Sipil, 2023)
This study aimed to reduce the torsion in the re-entrant structure that occurs due to the eccentricity distance between the center of mass and the center of rigidity. Three types of structures are modeled, namely regular structure (model A), re-entrant irregularity structure (Model B), and re-entrant irregular structure with shear wall strengthening (B-SWA). The shear wall strengthening in the B-SWA model is designed for dimensional optimization using the Nelder-Mead Algorithm method with MatLab software. Running output from the fminsearch function on MatLab, the optimal shear wall dimensions for the B-SWA model are L1 = 2.2317 m, L2 = 1.1611 m.The results of the structural analysis using the ETABS software show that the shear wall optimization carried out on the B-SWA model has succeeded in increasing the stability of the structure, namely the results of the capital mass ratio participation show a similar pattern to model A, namely in SumUX the value of 0.9019 has been reached in modal 7. Modeling optimal shear wall after performance review with pushover analysis shows that the performance of the B-SWA model has succeeded in increasing the performance seen from the Base Shear vs. Monitored Displacement value compared to models A and B.